Analysis of the influence of introductory instruction time in virtual reality on the effects of the training - Szymon Łagosz; Jacek Grabowski; Vaclav Dombek (Edukacja Ustawiczna Dorosłych)
The study described in this paper is focused on the attempt to determine the optimal time that should be devoted to introductory instructions provided in immersive virtual reality (IVR) in order to use the time dedicated to the entire training process in the most effective way possible. It was assumed that instruction efficiency would be determined by the number of mistakes committed and the time taken to successfully accomplish the test task intended to examine the course participants’ ability to use the IVR application and to apply theoretical knowledge in IVR-based practical exercises. To conduct the planned study, it was assumed that there is an optimal time that is worth devoting to instructions in IVR, and that exceeding this time does not yield any further measurable effects in the form of a significantly reduced number of mistakes committed and shortened time taken to successfully accomplish the test task. The study was conducted during VR training courses.